Penggunaan Alat Peraga Untuk Pengenalan Kesehatan Organ Reproduksi Pada Remaja Putri - Arfiani; Andi arfah; Andi hariati; Rahmaniyah R; Antonius Ali Wutun (JCS, 2024)
Adolescence is a transition period from childhood to adulthood. During this period, adolescents experience changes both on the outside and inside of the body, both changes in body structure and function. Adolescence begins with very rapid growth which is usually called puberty. Problems related to reproductive health often stem from a lack of information, understanding and awareness to achieve reproductive health. There are many things related to this, starting from an introduction to reproductive organs, an understanding of the need to maintain the cleanliness of reproductive organs, an understanding of reproductive processes and the impact of irresponsible behavior. Therefore, providing an understanding of the health of reproductive organs and their functions as well as how to maintain health for teenagers is necessary. The aim of this activity is to increase female students' knowledge about Introduction to Reproductive Organ Health in Adolescents by using teaching aids. Using preparation, implementation and evaluation methods, the value obtained increased after introducing the reproductive organs and their functions as well as how to maintain and care for them. From these results it can be proven that providing education has a positive impact, namely increasing female students' knowledge. And the use of teaching aids is very helpful according to the results of this PKM activity. The use of props for female reproductive organs in counseling can increase female students' knowledge.